Analysis result of hair straighteners - C. Santa Bárbara, Maria (2008)
Hair-straightening products are subjected by the Brazilian enforced law to obligatory registration, as they contain irritating substances in their composition. Straightening is classified as either a commercial or a professional product according to the maximum rates allowed by Brazilian legislation. With the growing occurrence of products containing actives above legal limit, as well as the inadequate use of substances, the present work aimed to communicate the primary problems found in the samples analyzed in the Adolfo Lutz Institute between 2003 and 2007 concerning the active principle rate compared with the enforced law and the adverse effects reported by consumers. Thirty-eight hair-straightening samples of different trade marks with different actives, collected by Sanitary Inspection, PROCON and Criminology Institute, were tested, whereof 20 (52.63%) either surpassed actives maximum legal limit or contained excessive formaldehyde rates, the formaldehyde in cosmetics is only permitted as a conserver or in nail-hardening products.